2016
DOI: 10.7883/yoken.jjid.2014.323
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between MMP Expression and Virulence of Dengue Virus Type-2 in Infected Mosquito and Mammalian Cells

Abstract: SUMMARY:Dengue virus infections are mostly asymptomatic but can produce a mild, self-limiting acute febrile illness, dengue fever, or a life threatening severe illness, dengue hemorrhagic fever. Dengue hemorrhagic fever is associated with increased vascular permeability partly as a result of elevated levels of matrix metalloproteinases (MMPs). We characterized MMP-2 and MMP-9 production in mosquito and mammalian cells after infection with three strains of dengue virus type-2 (D2-) ranging in virulence: 16681, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In humans, increased MMP activity is associated with increased pathogenicity, as MMPs assist in breaking down the basal lamina of tissues, allowing for subsequent viral entry and replication, often resulting in increased vascular leakage. 21 In mosquitoes, MMPS have been implicated in extracellular matrix remodelling, potentially allowing virions to pass through an altered basal lamina. 22 MMPs also have been annotated as anti-viral, acting as apoptotic effectors in the important anti-viral JAK-STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, increased MMP activity is associated with increased pathogenicity, as MMPs assist in breaking down the basal lamina of tissues, allowing for subsequent viral entry and replication, often resulting in increased vascular leakage. 21 In mosquitoes, MMPS have been implicated in extracellular matrix remodelling, potentially allowing virions to pass through an altered basal lamina. 22 MMPs also have been annotated as anti-viral, acting as apoptotic effectors in the important anti-viral JAK-STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…92 There are still very limited studies that showed the linkage of the immune system with matrix metalloproteinases. 93 However, some studies have shown that there is a role of immune cells and their mediators in the regulation of MMPs in dengue viral disease especially DSS. We, for the first time, have shown that there is a very important role of monocytes in mediated MMPs expression in response to dengue viral NS-1 protein.…”
Section: Role Of Immune System In the Dengue Pathogenesis And Its Cor...mentioning
confidence: 99%
“…There are still very limited studies that showed the linkage of the immune system with matrix metalloproteinases 93 . However, some studies have shown that there is a role of immune cells and their mediators in the regulation of MMPs in dengue viral disease especially DSS.…”
Section: Introductionmentioning
confidence: 99%